Correlational Study of Media Content as Catalyst of Violent Behaviour Among Youths in Abraka Metropolis - Ivwighren, Hannah; Chukwuebueni, Florence Oghenekome (The Indonesian Journal of Social Studies, 2024)
This paper spotlights the rising concern of youths exhibiting violent behaviour. The scope is on cultivation and social learning theories linked to and rationalizing media content as catalysts of violent behaviour among the youths. With the aid of primary data sources for analysis, 180 questionnaires were printed and distributed to senior school students in Abraka metropolis. 178 filled questionnaires came back but 2 were incomplete so were discarded. 176 were used. Cultivation theory was identified as a theory that incites learning and practicing what a person sees on television while the social learning theory points out observation, imitation, and modeling as ways of learning. Empirical studies were also reviewed to establish other researchers’ views and their findings were scrutinized in line with this paper on how media content encourages copycatting into real life. The researchers made some recommendations to the government, media houses, and institutions of learning but, specifically to the youths to be more responsible and selective of the content they expose themselves to and consume or to be ready to face immediate and severe punishment if found guilty of violent behaviour.